Gyrator transform based double random phase encoding with sparse representation for information authentication. (July 2015) - Chen, Jun-xin; Zhu, Zhi-liang; Fu, Chong; Yu, Hai; Zhang, Li-bo
Abstract: Optical information security systems have drawn long-term concerns. In this paper, an optical information authentication approach using gyrator transform based double random phase encoding with sparse representation is proposed. Different from traditional optical encryption schemes, only sparse version of the ciphertext is preserved, and hence the decrypted result is completely unrecognizable and shows no similarity to the plaintext. However, we demonstrate that the noise-like decipher result can be effectively authenticated by means of optical correlation approach. Simulations prove that the proposed method is feasible and effective, and can provide additional protection for optical security systems. Highlights: An optical information authentication approach is proposed. Only the sparse version of the ciphertext is preserved for authentication. The noise-like decipher image can be authenticated with optical correlation means. The proposed method can provide additional protection to optical security systems.